Emotions and Illocutionary Acts Used by Polytechnic Students in Describing Online Learning Issue - Zainal Arifin Renaldo (ELT-Lectura, 2021)
As COVID-19 Pandemic hit the world, many fields of life need to face some changes. One of the affected areas is academic activity. Since the beginning of the outbreak, academic activity has been switched from class meeting to online meeting. There are various reactions towards the change of academic behavior among students. This article is aimed at classifying the emotions carried out in illocutionary acts used by the students of Politeknik Caltex Riau in regards to online learning issue which manifest in their writing. This research is a descriptive qualitative analysis in which data were collected from students’ essay writing under the selected topic. From 30 articles of students’ essay writing, 59 sentences were taken as data source. In analyzing the emotional classification, Goleman’s theory of emotional intelligence is used. Together with this theory, Speech Acts Theory by Yule (2000) and Illocutionary Acts Theory by Searle (1997) are used. The result of the study shows that there are four kinds of illocutionary acts used by the students in their writing with expressives appeared to be the most frequent illocutionary acts followed by representatives, directives and commissives respectively. There are five emotional classifications manifest in students’ writing i.e. love, anger, enjoyment, sadness, and irritability. Illocutionary acts, emotions